THE PUBLIC LEADERSHIP OF BUNDO KANDUANG AS AN EFFORT TO PREVENT THE RADICALISM MOVEMENT IN WEST SUMATRA - Hilma Pami Putri (Universitas Islam Negeri Imam Bonjol Padang, 2021)
West Sumatra as the basis of religious movements in Indonesia is fertile ground for the birth of radical understanding. This also has an impact on the survival of the Minangkabau people who prioritize tolerance in their daily lives. One of the local wisdom of the Minangkabau people and included in the ranks of government is Bundo Kanduang. According to Bundo Kanduang, this radicalism understanding is very contrary to the doctrine of the Minangkabau which bases on Adat Basandi Syara’ Syarak Basandi Kitabullah so that intolerant does not have space to be developed in West Sumatra. This research is a descriptive qualitative analysis research that explores and explains about Bundo Kanduang public leadership in overcoming the Radical Movement in West Sumatra. In this research, it was found that the efforts made by Bundo Kanduang were 1. Become an agent of peace in the community. 2. Actively providing counseling and guidance in cyberspace and the real world about the dangers of radical understanding to the young generation. 3. Synergism Bundo Kanduang’s role in Minangkabau to maintain children’ nationality and integrity.